PENGARUH LKS IPA TERPADU BERBASIS WEB DENGAN MENGINTEGRASIKAN NILAI KARAKTER PADA MATERI GLSTSGPS TERHADAP KOMPETENSI SISWA KELAS VIII SMPN 8 PADANG - Ayu Triana; Asrizal Asrizal; Zulhendri Kamus (Universitas Negeri Padang, 2016)
Integrating Science, ICT, and character values in learning are important in education. The fact of this integration is not done optimal in school. Alternative solution of this problem is use of student worksheet based web by integrating character values in the learning of natural science. The purpose of this research is determine the competence of students in learning by using of student worksheet based web by integrating character values in the learning of natural science in materials linear motion, structure of plan, motion system, simple machine and investigate the impact of student worksheet based web by integrating character values in the learning of natural science in materials linear motion, structure of plan, motion system, simple machine the competence of students class VIII SMPN 8 Padang. The kind of this reseach is the quasi experiment research. The population of this research were all of the students of SMPN 8 Padang of academic year 2014/2015. Sampling technique was purposive sampling. The data of the research were the competence of students on aspects of knowledge, attitudes, and skills. Research instrument in the form of sheets of learning outcomes assessment, observation sheets, and performance assessment sheet. Based on data analysis of research that has been done can be stated that the results of this study are: competence of students in learning by use of student worksheet based web by integrating character values in the learning of natural science on aspects of knowledge, attitudes, and skills respectly 76.17, 81.60, and 89.84. Second, the use of student worksheet based web by integrating character values in the learning of natural science in materials linear motion, structure of plan, motion system, simple machine give effect to the competence of students class VIII SMPN 8 Padang